2003
DOI: 10.4269/ajtmh.2003.69.11
|View full text |Cite
|
Sign up to set email alerts
|

Application of Molecular Tools in the Control of Blinding Trachoma

Abstract: Abstract. The use of anti-chlamydial antibiotics for trachoma control is based on the assumption that most people with clinically active disease have conjunctival infection with Chlamydia trachomatis. In high prevalence areas, this is generally true. As prevalence decreases, however, the positive predictive value of clinical signs for C. trachomatis infection also decrease. In this paper, the case for using laboratory assays to guide trachoma control strategies is presented, molecular methods for diagnosis (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…2 There has been a concomitant increased interest in diagnostic advances, including the potential applications of molecular testing. 3 DNA detection of C. trachomatis using the polymerase chain reaction (PCR) has been used to define the epidemiology of trachoma infections and to assess the effectiveness of mass treatment with azithromycin. 3,4 Insight into the molecular epidemiology of trachoma in the Northern Territory was recently provided by genetic studies characterizing the C. trachomatis outer membrane protein 1 (omp1) gene, which suggested that evolutionarily distinct strains of Ba and C serotypes are responsible for trachoma disease in northern Australia.…”
Section: Introductionmentioning
confidence: 99%
“…2 There has been a concomitant increased interest in diagnostic advances, including the potential applications of molecular testing. 3 DNA detection of C. trachomatis using the polymerase chain reaction (PCR) has been used to define the epidemiology of trachoma infections and to assess the effectiveness of mass treatment with azithromycin. 3,4 Insight into the molecular epidemiology of trachoma in the Northern Territory was recently provided by genetic studies characterizing the C. trachomatis outer membrane protein 1 (omp1) gene, which suggested that evolutionarily distinct strains of Ba and C serotypes are responsible for trachoma disease in northern Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are individuals with clinical signs of active disease in whom the organism cannot be detected and, conversely, C. trachomatis can be found in specimens from individuals lacking the characteristic signs and symptoms. This raises the question of the usefulness of the available microbiological tests as complementary aids for clinical diagnosis and epidemiological surveys [6].…”
Section: Introductionmentioning
confidence: 99%
“…They are extremely useful for detecting, quantifying, and genotyping C. trachomatis DNA (124). The nucleic acid amplification tests will there- fore continue to improve our understanding of the pathogenesis of infection, the role that persistent infection plays in the development of the blinding complications of trachoma, the epidemiology of ocular infection, and the impact of interventions designed to control trachoma blindness.…”
Section: Which Laboratory Tests Are Useful?mentioning
confidence: 99%